Reviewing the role of positive classroom climate in improving English as a foreign language students’ social interactions in the online classroom - Qiu, Fei (Frontiers in Psychology, 2022)
The teacher and learners are cooperatively involved in the creation of a positive climate in an L2 class. In the online language learning environment today, teachers can make the best use of technology, multimedia learning, and accessibility of learners to create a supportive and effective climate. In this productive climate, the teacher and learners can have multiple forms of social interaction which can improve language learners’ communicative skills. Not only can the teacher expect better learning outcomes, but s/he can also ensure students’ wholehearted attendance in, attention to, and participation in class activities. A positive class climate and the consequent better social interactions can also enhance learners’ affective well-being. For example, higher self-esteem leads to lower levels of anxiety and better emotional health. This study aims to review the contribution of a positive classroom climate to the improvement of students’ social interaction in the online L2 classroom. To do this, the findings of the relevant studies have been presented and their implications for the construction of a positive online L2 classroom climate have been provided. Suggestions are made on how to help teachers create a positive climate in online L2 classes and how to pave the way for more effective social interactions between teachers and students and among students. Also, implications are provided for L2 teachers, researchers, and trainers, especially in the post-pandemic era.